VD_FINDINFO Décision / 2014 / 134 vom 11. Februar 2014 - VD Tribunal cantonal (2014)
DIFFAMATION, CALOMNIE, FAUX TÉMOIGNAGE, ABUS D'AUTORITÉ, DÉCISION D'IRRECEVABILITÉ | 173 CP, 174 CP, 183 CP, 307 CP, 312 CP, 310 CPP (CH)